2018
DOI: 10.1177/2050640617752182
|View full text |Cite
|
Sign up to set email alerts
|

Results of surveillance in individuals at high‐risk of pancreatic cancer: A systematic review and meta‐analysis

Abstract: Surveillance programs identify successful target lesions in 3.3% of HRIs with a similar yield of EUS and MRI and an annual risk of 0.5%. A higher rate of target lesions was reported in HRIs with specific DNA mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
1
36
0
4
Order By: Relevance
“…In a large family cohort study, Win et al subsequently confirmed that FDRs of LLS cases have a higher CRC risk compared FDRs of sporadic pMMR CRC cases, but a lower risk compared with FDRs of LS cases 23. Compared with FDRs of sporadic pMMR CRC cases, a higher risk of CRC was estimated for FDRs of LLS cases (HR 2.06, 95% CI 1.59 to 2.67), and an even higher risk for the FDRs of LS cases (HR 5.37, 95% CI 4.16 to 6.94) 23 119 140 155–162…”
Section: Lynch-like Syndromementioning
confidence: 95%
See 1 more Smart Citation
“…In a large family cohort study, Win et al subsequently confirmed that FDRs of LLS cases have a higher CRC risk compared FDRs of sporadic pMMR CRC cases, but a lower risk compared with FDRs of LS cases 23. Compared with FDRs of sporadic pMMR CRC cases, a higher risk of CRC was estimated for FDRs of LLS cases (HR 2.06, 95% CI 1.59 to 2.67), and an even higher risk for the FDRs of LS cases (HR 5.37, 95% CI 4.16 to 6.94) 23 119 140 155–162…”
Section: Lynch-like Syndromementioning
confidence: 95%
“…The goal of screening is to identify and treat early stage pancreatic cancers (T1N0M0) and high-risk precursor lesions, high-grade pancreatic intraepithelial neoplasia (PanIN-3) and intraductal papillary mucinous neoplasia (IPMN) with high-grade dysplasia. Signoretti et al conducted a systematic review and meta-analysis of 16 pancreatic surveillance studies in high-risk groups 157. A relatively low diagnostic yield of pancreatic cancers and relevant precursor lesions was reported (3.3%) using endoscopic ultrasound and MRI as first line screening tests.…”
Section: Lynch Syndromementioning
confidence: 99%
“…Numerous studies in the past have failed to show a substantial benefit of screening for pancreatic cancer [ 21 ]. More recent studies offered suggestions of benefit in at least some high-risk patients and it is reasonable that stronger evidence supporting surveillance in HRIs derive from long-term follow-up studies compared to single-round ones [ 51 , 52 , 53 , 54 , 55 ]. Currently, no protocols are established, and disagreement remains as to the best screening modality, time of screening initiation or follow-up duration.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…In 3.3% of high-risk individuals, lesions are successfully detected, which indicates promising results [111]. Corral et al [112] summarized in a meta-analysis that 135 patients at high-risk for pancreatic cancer have to be screened to identify 1 patient with a high-risk pancreatic lesion.…”
Section: Considerationmentioning
confidence: 99%